Methylome Analysis in Nonfunctioning and GH-Secreting Pituitary Adenomas - Giuffrida, Giuseppe; D’Argenio, Valeria; Ferraù, Francesco; Lasorsa, Vito Alessandro; Polito, Francesca; Aliquò, Federica; Ragonese, Marta; Cotta, Oana Ruxandra; Alessi, Ylenia; Oteri, Rosaria; Di Maggio, Federica; Asmundo, Alessio; et al. (Frontiers in Endocrinology, 2022)
Pituitary adenomas (PAs), usually benign lesions, can sometimes present with “aggressive” features (rapid growth, local invasiveness, scarce response to conventional treatments). Despite a few genetic alterations have been associated to this clinical behaviour, the role of epigenetic modifications, mainly methylation and miRNAs activity, is now opening new frontiers in this field. We evaluated the methylation profile of 21 PAs (11 GH-omas, 10 non-functioning tumors – NFPAs) samples from TNS surgery and 5 normal pituitaries, collected at our neurosurgery between 2015 and 2017. DNA was extracted and sequenced, selecting 184,841 target regions. Moreover, methylation profiles were correlated with demographic, radiological, and clinico-pathological features. NFPAs showed higher methylation levels vs GH-omas, with 178 differentially methylated regions (DMRs) mainly consisting of non-coding and intronic sequences, and mostly localized in the open sea regions. We also found three hypermethylated genes (C7orf50, GNG7, and BAHCC1), involved in tumorigenesis processes and potentially influencing pituitary tumors pathophysiology. Among clinico-pathological features, only the maximum diameter resulted significantly higher in NFPAs. Our data provide further evidence of the complex epigenetic background of pituitary tumors. In line with the current literature, we confirmed a significant prevalence of hypermethylation in NFPAs vs GH-omas, whose pathophysiological consequence is yet to be defined.